Influence of land-use systems on hydraulic properties of soils in Yenagoa and Amassoma, Bayelsa State, Nigeria - Agbai, W.P.; Kosuowei, M.T. (International Journal of Environment, 2022)
This research aimed to determine the effect of different land-use systems on the matric potential, and hydraulic conductivity of the soils of Yenagoa and Amassoma communities. Soil samples were collected from four respective land-use types namely: Fallow land, Oil Palm Plantation, Plantain Plantation, and Virgin land. A total of 12 samples were bulked from three replicates at each land use type and were collected at depths of 0-15cm, 15-30cm, and 30-45cm respectively. The samples were taken to the laboratory to analyze their physical, chemical, and hydrological properties. The result showed that the different land use had a significant effect (P<0.05) on some soil physical, chemical, and hydraulic characteristics. The different land-use systems had a significant effect on the soil hydraulic conductivity with the highest in virgin (13.6 cm/hr) and lowest in the plantain plantation (7.6 cm/hr). The virgin land recorded the highest Soil Water Holding Capacity (SWHC) of 2.85 cm with a range of 1.55 – 2.85cm and Plant Available Water Capacity (PAWC) of 0.19 cm3cm-3, with a range of 0.10 - 0.19 cm3cm-3, while the plantain plantation recorded the lowest (1.55 cm and 0.10 cm3cm3). Based on the study, it is recommended that soils with high Plant Available Water Capacity (PAWC) and Soil Water Holding Capacity (SWHC) be used to cultivate crops that are non-tolerant to water stress while organic amendments are used on soils with low fertility.